THE USE OF SMART PHONES TO IMPROVE SPEAKING SKILLS AND TO DEVELOP INDEPENDENT LEARNERS - Iyehezkiel, Iyehezkiel; Wiradisastra, Grace J. Tiwon (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
Speaking is one of the four language skills that is often considered the most difficult to master properly because it includes various components, namely accuracy, fluency, comprehensiveness and content. Nevertheless, the time allocated for speaking skills in English Study Programs is very limited, in addition the classes are usually large. Therefore, it was necessary to find a language teaching method that could overcome this condition. This research has implemented language learning with the help of cellphones or MALL (Mobile Assisted Language Learning). The research also introduced the concept of independent learning to the students to train them to be come independent learners. This would enable them to continue to improve their speaking English and other language skills after completing their university education. Independent learning would also help them keep up with the times and become life-long learners so that they are always able to keep up with the rapid development in this era. This research is a quasi experimental research in which the subjects were the students of two second semester classes of the English Study Program. The experimental class was introduced to independent learning and both classes used MALL for the class sessions. A pre-test and post test were used to measure the improvement of students’ speaking proficiency. In addition, a questionnaire on their perceptions of using MALL in distance learning and independent learning. This was supported by qualitative data obtained through, student journals, observations and interviews. The results showed that the students doing extra activities using MALL did not show significant increase in the post test results, nevertheless good improvement was made in pronunciation and intonation.